Performer la visite d'un quartier et transformer la perception des lieux (Itinera, 2023)
In July 2022, the artist Anne-Sophie Turion realizes the tour-performance Grandeur Nature in two districts of Rennes. Instead of commenting on the built heritage, as one might have expected in the context of an urban tour, the performer restores the lived stories of the inhabitants of the neighborhoods. Based on the analysis of this artistic proposal, the article seeks to understand how the device contributes to reconfiguring the perception of the urban territory covered. We are interested in how performance reveals spaces as they are occupied and perceived by users ; then we try to show the links that the proposal weaves between the protagonists and we try to understand to what extent the common experience of the neighborhoods crossed contributes to create social ties.